Effect of Delayed Admission to Intensive Care Units from the Emergency Department on the Mortality of Critically Ill Patients - SABAZ, NAGİHAN (KOWSARMEDICAL, 2020)
Background: Increasing in emergency department need to critical care, the number of intensive care unit bed worldwide is inadequate to meet these applies. Objectives: The aim of this study was to investigate the effect of waiting for admission to the Intensive Care Unit (ICU) in the Emergency Department (ED) on the length of stay in the ICU and the mortality of critically ill patients. Methods: This retrospective cohort study carried out between January 2012 - 2019 patients admitted to the ICU of a training and research hospital. The data of 1297 adult patients were obtained by searching the Clinical Decision Support System. Results: The data of the patients were evaluated in two groups as those considered to be delayed and non-delayed. It was determined that the delay of two hours increased the risk of mortality 1.5 times. Hazard Ratios (HR) was 1.548 (1.077 - 2.224). Patients whose ICU admission was delayed by 5 - 6 hours were found to have the highest risk in terms of mortality (HR = 2.291 [1.503 - 3.493]). A statistically significant difference was found in the ICU mortality, 28-day and, 90-day mortality between the two groups. ICU mortality for all patients' general was 25.2% (327/1297). This rate was 11.4% (55/481) in the non-delayed group and 33.3% (272/816) in the delayed group (P < 0.001). The 28-day mortality rate for all patients' general was 26.9% (349/1297). This rate was found to be 13.5% (65/481) in the non-delayed group and 34.8% (284/816) in the delayed group (P < 0.001). The 90-day mortality for all patients' general was 28.4% (368/1297). This rate was 14.1% (68/481) in the non-delayed group and 36.8% (300/816) in the delayed group (P < 0.001). Conclusions: Prolonged stay in the ED before admission to the ICU is associated with worse consequences, and increased mortality.
Keywords: Critically Patients; Delayed Admission; Emergency Department; Intensive Care Unit; Mortality Rate; LENGTH-OF-STAY; HOSPITAL MORTALITY; MEDICAL PATIENTS; STROKE PATIENTS; GOLDEN HOUR; IMPACT; TIME; OUTCOMES; DECISIONS